The Combined Effect of Counterpressure and Hypnobirthing on Reducing Labor Pain - Oktiningrum, Mudy (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Labor pain is pain caused by uterine contraction that can cause sympathetic nervous system activity to increase. Labor pain can also cause physiological changes in the body such as blood pressure rising, heart rate increasing, and respiratory rate increasing, and if this pain is not addressed immediately, it will cause more anxiety, tension, fear, and stress. this therapy aims to observe how the two approaches can work together to make labor more comfortable and less traumatic and help reduce pain during labor. This literature review examines the combined effects of counterpressure and hypnobirthing on labor pain reduction. Relevant articles from PubMed, Science Direct, and Google Scholar. The result showed that the average pain scale was on a severe scale before counterpressure and hypnobirthing, but on a moderate scale after counterpressure and hypnobirthing. This way, it will reduce pain and make you feel comfortable during contractions or between contractions. Based on the analysis that has been done by the author, it can be concluded that the use of counterpressure and hypnobirthing techniques is effective for reducing labor pain